2014
DOI: 10.1038/ja.2014.150
|View full text |Cite
|
Sign up to set email alerts
|

Mutant prevention concentrations of levofloxacin, pazufloxacin and ciprofloxacin for A. baumannii and mutations in gyrA and parC genes

Abstract: Fluoroquinolones are antimicrobial agents that are widely used clinically, but the increasing resistance of Acinetobacter baumannii (A. baumannii) to these agents is a matter of concern. We investigated mutant prevention concentrations (MPCs) of three fluoroquinolones, levofloxacin (LVX), pazufloxacin (PAZ) and ciprofloxacin (CIP). We analyzed an A. baumannii standard strain (ATCC19606) for mutation prevention indices (MPIs), MPCs and mutant selection windows as well as MICs of CIP, PAZ and LVX and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In the case of parC, all isolates possessed more than seven different silent mutations. The numbers of silent mutations within parC gene was higher than gyrA gene (47 vs. 12) as also observed in previous studies (Sun et al, 2015). The function of these mutations is still unknown.…”
Section: Mutations Within Qrdr Of Gyra and Parcsupporting
confidence: 79%
“…In the case of parC, all isolates possessed more than seven different silent mutations. The numbers of silent mutations within parC gene was higher than gyrA gene (47 vs. 12) as also observed in previous studies (Sun et al, 2015). The function of these mutations is still unknown.…”
Section: Mutations Within Qrdr Of Gyra and Parcsupporting
confidence: 79%
“…In the course of the same assessment [34], an attempt at the identification of carbapenemase genes was started, based on three multiplex PCRs targeting 11 carbapenemase genes, which had been originally designed for carbapenem-resistant Enterobacteriaceae [35]. As the resistance mechanisms typically abundant in A. baumannii were not covered by this approach, and known resistance mechanisms against fluoroquinolones in A. baumannii were not even addressed [36], the approach failed to identify the genetic background of the phenotypically observed resistance of the isolates.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that these two mutations are enough to predict resistance to CIP and LEV 48 . However, gyrA and parC mutations did not occur in all resistant mutant strains and the resistance may be attributed to changes in outer membrane protein expression and drug efflux pumps 50 . All tested isolates had a silent mutation in one or more positions of either gyrA or parC or even both gyrA and parC that do not lead to a change in amino acid composition.…”
Section: Discussionmentioning
confidence: 90%